Polymonad programming in Haskell - Bracker, Jan; Nilsson, Henrik (2016)
Polymonads were recently introduced by Hicks et al. as a unified approach to programming with different notions of monads. Their work was mainly focussed on foundational aspects of the approach. In this article, we show how to incorporate the notion of polymonads into Haskell, which is the first time this has been done in a full-scale language. In particular, we show how polymonads can be represented in Haskell, give a justification of the representation through proofs in Agda, and provide a plugin for the Glasgow Haskell Compiler (GHC) that enables their use in practice. Finally, we demonstrate the utility of our system by means of examples concerned with session types and the parameterized effect monad. This work provides a common representation of a number of existing approaches to generalized monads in Haskell.